3D Imaging Segmentation and 3D Rendering Process for a Precise Puncture Strategy During PCNL – a Pilot Study - Durutović, Otaš; Filipović, Aleksandar; Milićević, Katarina; Somani, Bhaskar; Emiliani, Esteban; Skolarikos, Andreas; Janković, Milica M. (Frontiers in Surgery, 2022)
Percutaneous nephrolithotomy (PCNL) is frequently used as the first-line treatment of large and complex stones. The key point for successful complex stone removal with minimal risk of complications is to establish the most appropriate access route. Understanding the three-dimensional (3D) relationship of kidney stones and renal collecting systems is crucial for planning and creating an optimal access route. By using a 3D volume segmentation tool a more accurate approach to the renal collecting system and stone treatment could be planned. The objective of this study was assessing the impact of 3D software in getting the desired access.